Live surgery of colorectal endometriosis broadcasted from a surgeon's routine operating theater is not associated with higher complications rate. (21st September 2021) - Roman, Horace; Prosszer, Maria; Marabha, Jamil; Merlot, Benjamin; Forestier, Damien; Noailles, Myriam; Marpeau, Loïc; Tuech, Jean‐Jacques
Abstract: Introduction: Although live surgeries are routinely included in surgical congress programs, they are the subject of an ongoing debate in terms of patient safety and teaching value. The goal of our study was to assess the risk of postoperative complications related to live surgery broadcast from the surgeon's routine theater, in patients managed for deep endometriosis infiltrating the digestive tract. Material and methods: We report a retrospective comparative study, enrolling women managed for colorectal endometriosis by a gynecologic surgeon, from September 2013 to March 2020 in two referral centers. We compared the rate of postoperative bowel fistula in women managed during live surgery in the routine operating theater, with that observed in women for whom surgery was not broadcast. Results: Among 813 women, 33 (4.1% of cases) underwent surgical procedures transmitted live to various conference rooms located outside the hospital and were compared with 780 patients who underwent non‐broadcast surgery. Women's age, body mass index, past surgical and obstetrical history, and major preoperative complaints were comparable. Cases presented with impaired constipation score, more frequent sciatic pain, and infiltration of the vagina, whereas overall revised American Fertility Society classification scores were more severe in controls. The rate of rectal nodules over 3 cm in size was comparable between the two groups (72.7% in cases vs. 72.1% in controls). Operative time was also comparable (153 ± 52 minutes vs. 148 ± 79 minutes). Cases were more frequently managed by disk excision of rectal nodules (63.7% vs. 30.3%), and more frequently involved the sacral plexus (18.2% vs. 7.3%). Postoperative complications were comparable between the two groups, in terms of bowel fistula (3% in the live surgery group vs. 4.1% in controls), pelvic abscess requiring secondary laparoscopy (3% vs. 4.9%), or bladder dysfunction requiring self‐catheterization after discharge (6.1% vs. 5.3%). Conclusions: Performing laparoscopic management of colorectal endometriosis with live transmission of surgery from a surgeon's routine operating theater, is not related to a higher risk of major postoperative complications.